Interaction of picolinamide fungicide primary metabolites UK‐2A and CAS‐649 with the cytochrome bc1 complex Qi site: mutation effects and modelling in Saccharomyces cerevisiae. Issue 6 (29th April 2022) - Young, David H; Meunier, Brigitte; Wang, Nick X
Abstract: BACKGROUND: Fenpicoxamid and florylpicoxamid are picolinamide fungicides targeting the Qi site of the cytochrome bc 1 complex, via their primary metabolites UK‐2A and CAS‐649, respectively. We explore binding interactions and resistance mechanisms for picolinamides, antimycin A and ilicicolin H in yeast by testing effects of cytochrome b amino acid changes on fungicide sensitivity and interpreting results using molecular docking. RESULTS: Effects of amino acid changes on sensitivity to UK‐2A and CAS‐649 were similar, with highest resistance associated with exchanges involving G37 and substitutions N31K and L198F. These changes, as well as K228M, also affected antimycin A, while ilicicolin H was affected by changes at G37 and L198, as well as Q22E. N31 substitution patterns suggest that a lysine at position 31 introduces an electrostatic interaction with neighbouring D229, causing disruption of a key salt‐bridge interaction with picolinamides. Changes involving G37 and L198 imply resistance primarily through steric interference. G37 changes also showed differences between CAS‐649 and UK‐2A or antimycin A with respect to branched versus unbranched amino acids. N31K and substitution of G37 by large amino acids reduced growth rate substantially while L198 substitutions showed little effect on growth. CONCLUSION: Binding of UK‐2A and CAS‐649 at the Qi site involves similar interactions such that general cross‐resistance between fenpicoxamid and florylpicoxamid is anticipated in target pathogens. Some resistance mutations reduced growth rate and could carry a fitness penalty in pathogens. However, certain changes involving G37 and L198 carry little or no growth penalty and may pose the greatest risk for resistance development in the field. © 2022 Society of Chemical Industry Abstract : Target site interactions and potential resistance mechanisms for the QiI picolinamide fungicides were explored by analysing effects of amino acid substitutions on fungicide sensitivity and molecular docking studies.